Oral History Interview: Catherine Sullivan - Sullivan, Catherine
Born in Los Angeles, Sullivan came to Bakersfield in 1939 as a social worker for the State Relief Administration. She provides personal anecdotes of people she tried to help. Sullivan also describes the forms of relief provided under New Deal programs like the WPA. After 1941 she worked in the Kern County Welfare Department to help families with dependent children. Her account includes examples of prejudicial actions against Okies and Arkies and how migrants survived their hardships. She also comments on the differences between the government camps and the grower supplied camps.